PENGARUH GADGET TERHADAP PERKEMBANGAN ANAK USIA DINI - Pratama, Dwi Wahyu Yudha (UNIVERSITAS SERAMBI MEKKAH, 2024)
Gadgets are media that are used every day as new tools in science and technology development programs. The presence of gadgets will certainly bring changes in interpersonal relationships. Now, communication activities are increasingly developing with the emergence of devices. These include smartphones such as iPhone, Android, Blackberry and notebooks. In psychology, children aged 0-6 years are considered early childhood education. These devices influence the social development of early childhood. The impact of gadget use on the social development of early childhood has positive and negative impacts. Excessive use of gadgets will have a negative impact on children's social and emotional development. The negative impacts of device use on children include withdrawal, sleep disturbances, feelings of loneliness, violent behavior, waning creativity, and the risk of cyberbullying. This approach uses a type of quantitative research with a survey method, namely collecting data using a list of statements and giving it to respondents to answer. Apart from that, researchers also use observation to directly observe the behavior of young children. Then the researchers looked at the overall results of the questionnaire, observations and then the researchers were able to find conclusions regarding the factors that gadgets have that have a big influence on early childhood.